Contrasting reproductive strategies of triploid hybrid males in vertebrate mating systems - Pruvost, N B M; Mikulíček, P; Choleva, L; Reyer, H-U (Journal of evolutionary biology, 2015)
The scarcity of parthenogenetic vertebrates is often attributed to their 'inferior' mode of clonal reproduction, which restricts them to self-reproduce their own genotype lineage and leaves little evolutionary potential with regard to speciation and evolution of sexual reproduction. Here, we show that for some taxa, such uniformity does not hold. Using hybridogenetic water frogs (Pelophylax esculentus) as a model system, we demonstrate that triploid hybrid males from two geographic regions exhibit very different reproductive modes. With an integrative data set combining field studies, crossing experiments, flow cytometry and microsatellite analyses, we found that triploid hybrids from Central Europe are rare, occur in male sex only and form diploid gametes of a single clonal lineage. In contrast, triploid hybrids from north-western Europe are widespread, occur in both sexes and produce recombined haploid gametes. These differences translate into contrasting reproductive roles between regions. In Central Europe, triploid hybrid males sexually parasitize diploid hybrids and just perpetuate their own genotype--which is the usual pattern in parthenogens. In north-western Europe, on the other hand, the triploid males are gamete donors for diploid hybrids, thereby stabilizing the mixed 2n-3n hybrid populations. By demonstrating these contrasting roles in male reproduction, we draw attention to a new significant evolutionary potential for animals with nonsexual reproduction, namely reproductive plasticity.
Keywords: triploidie; Rana; sperm-dependent parthenogenesis; partenogeneze; hybridization; Europe; poměr pohlaví; zvířata; genetická variace; Slovakia; Czech Republic; all-hybrid population; sexual parasite; hybridogenesis; mikrosatelitní repetice; Slovenská republika; mužské pohlaví; Česká republika; Microsatellite Repeats; asexual reproduction; polyploidy; Parthenogenesis; Evropa; Reproduction; rozmnožování; gamete production; populační genetika; hemiclone; ženské pohlaví; Genetic Variation; Genetics, Population; Ranidae; Animals; Triploidy; Sex Ratio; Male; Female